What is brand? Some insights in the historical development - Ur Rehman, Fazal; Md Yusoff, Rosman; Ismail, Fadillah; Javed, Farwida (International Journal of Academic Management Science Research (IJAMSR), 2018)
The aim of this study is to enhance understanding in the philosophy of the brand along with its historical development around the world. Its main purpose is to clarify the nature of the brand, its origination, ancient phase, digital phase and the future of branding. This study is based on the secondary source to clarify the gap of knowledge, understand the thought of branding and review the literature in regard to its historical development and evaluation around the world. It has found that brand is a tangible and non-tangible asset of a business that presents a unique identity and reputation among a wide set of competitors, and is perceived as a market leader in a particular industry. The study has found that branding is the best practice to enhance the image and value of business among targeted consumers. It has anticipated that branding is the technique to gain competitive advantage and accomplish the objectives of a business. This study presents a comprehensive overview of the nature of branding along with its wide historical development (origin, ancient phase, digital phase, future phase) around the world.